PROTECTED‐UK – Clinical pharmacist interventions in the UK critical care unit: exploration of relationship between intervention, service characteristics and experience level. (4th October 2016) - Rudall, Nicola; McKenzie, Catherine; Landa, June; Bourne, Richard S.; Bates, Ian; Shulman, Rob
Abstract: Purpose: Clinical pharmacist (CP) interventions from the PROTECTED‐UK cohort, a multi‐site critical care interventions study, were further analysed to assess effects of: time on critical care, number of interventions, CP expertise and days of week, on impact of intervention and ultimately contribution to patient care. Methods: Intervention data were collected from 21 adult critical care units over 14 days. Interventions could be error, optimisation or consults, and were blind‐coded to ensure consistency, prior to bivariate analysis. Pharmacy service demographics were further collated by investigator survey. Key findings: Of the 20 758 prescriptions reviewed, 3375 interventions were made (intervention rate 16.1%). CPs spent 3.5 h per day (mean, ±SD 1.7) on direct patient care, reviewed 10.3 patients per day (±SD 4.2) and required 22.5 min (±SD 9.5) per review. Intervention rate had a moderate inverse correlation with the time the pharmacist spent on critical care ( P = 0.05; r = 0.4). Optimisation rate had a strong inverse association with total number of prescriptions reviewed per day ( P = 0.001; r = 0.7). A consultant CP had a moderate inverse correlation with number of errors identified ( P = 0.008; r = 0.6). No correlation existed between the presence of electronic prescribing in critical care and any intervention rate. Few centres provided weekend services, although the intervention rate was significantly higher on weekends than weekdays. Conclusions: A CP is essential for safe and optimised patient medication therapy; an extended and developed pharmacy service is expected to reduce errors. CP services should be adequately staffed to enable adequate time for prescription review and maximal therapy optimisation.